Study to increase the pneumococcal vaccination rates of individuals aged 65 years and older - Biyik, M. V. (Prim Health Care Res Dev, 2020)
BACKGROUND: In our study, we intended to observe the impact of recommending the pneumococcal vaccine to individuals who were called on the phone or interviewed face-to-face by their doctors on vaccination rates. METHODS: Two hundred individuals who were 65 years old and older were included in our study. They were questioned about their awareness regarding adult immunisation, and their knowledge level and vaccination statuses were determined regarding the tetanus, influenza, hepatitis, and pneumococcal vaccines. After they were given information about the pneumococcal vaccine, they were asked about their interest in being vaccinated. Those who agreed to be vaccinated were invited and vaccinated. RESULTS: According to the questionnaire, 150 people (75%) knew of the influenza vaccine, 130 people (65%) knew of the tetanus vaccine, 53 people (26.5%) knew of the hepatitis B vaccine, and 49 people (24.5%) knew of the pneumococcal vaccine. A total of five people (2.5%) had received the pneumococcal vaccine. Fifty-eight of 97 patients (59.8%) who completed the questionnaire during a phone call and 84 of 103 patients (81.6%) who completed the questionnaire during a face-to-face interview received the pneumococcal vaccine. As a result, the rates of pneumococcal vaccination increased from 2.5% before the study to 73.5% after the study. CONCLUSION: The findings show that the vaccination rates for pneumococcus were very low among our participants. The immunisation rates increased when doctors provided consultation to participants about adult immunisation.